Rockburst in Sandstone Containing Elliptic Holes with Varying Axial Ratios - Yang Wang; Manchao He; Dongqiao Liu; Yubing Gao (Advances in Materials Science and Engineering)
Rockburst disaster is one of the prominent problems faced by deep underground engineering. In this study, rockburst in four elliptical holes with different axial ratios in sandstone under biaxial loading is studied as an analogue for underground roadways. Video and acoustic emission (AE) equipment is used to monitor the biaxial loading tests. Experimental results indicate that each of the elliptical holes goes through four stages: quiet period, small particle ejection, spalling, and rockburst. The duration of quiet and spalling periods increased with increasing axial ratio of ellipse. The duration of the ejection and rockburst periods remains unchanged. All the four elliptical holes have V-shaped pits after rockburst occurs. The fragments produced during rockburst are divided into coarse, medium, fine, and micro grains. The quantity of coarse and medium grains increases with increasing axial ratio. The mass ratio of coarse and medium grains increases and that of fine and micro grains decreases. The depth, angle, and area of the V-shaped pits decrease with increasing axis ratio. Tensile cracks play an important role in rockburst failure. Tensile cracks are the dominant crack types formed during rockburst and account for over 70% of all cracks in the samples. The number of tensile cracks increased and the number of shear cracks decreased. This paper has some reference value for practical engineering design and prevention of rockburst.